Greater baseline serum C-reactive protein concentrations are associated with reduced survival in dogs receiving cyclophosphamide, doxorubicin, vincristine, and prednisone chemotherapy for primary nodal diffuse large B-cell lymphoma. (November 2022) - Childress, Michael O.; Christian, John A.; Ramos-Vara, José A.; Rosen, Nicole K.; Ruple, Audrey
Abstract: Prognostic factors for dogs with diffuse large B-cell lymphoma (DLBCL) are poorly characterized. Prior reports suggest that dogs with a systemic inflammatory response at the time of lymphoma diagnosis experience inferior survival times. However, no specific biomarkers of inflammation have been identified as prognostic indicators in dogs with DLBCL. Baseline C-reactive protein (CRP) concentrations were measured in banked sera from 91 dogs with chemotherapy-treated DLBCL using a commercially available laboratory assay. Associations between baseline serum CRP concentrations and other variables of potential prognostic significance with progression-free survival (PFS) were tested using Cox proportional hazards modeling. In the final multivariable model, only a complete (rather than partial) remission to chemotherapy (Hazard ratio [HR] 0.02; 95% confidence intervals [CI] 0.01–0.07; P < 0.001) and serum CRP concentration > 1.0 mg/dL (HR, 1.73; 95% CI, 1.02–2.92; P = 0.042) were significantly associated with PFS. The median PFS for dogs with CRP concentration ≤ 1.0 mg/dL (within the test reference interval) was 315 days, while that for dogs with CRP concentration > 1.0 mg/dL was 232 days ( P = 0.06). These results suggest that baseline serum CRP concentration is independently associated with progression-free survival in dogs with DLBCL, making it a potentially useful prognostic biomarker for dogs with this cancer. Highlights: Prognostic factors for dogs with diffuse large B-cell lymphoma (DLBCL) are unclear. DLBCL associated with systemic inflammation may have a worse prognosis. C-reactive protein (CRP) measured in pre-treatment sera from 91 dogs with DLBCL. Increased serum CRP at baseline was associated with reduced survival.